1999
DOI: 10.1097/00007890-199905150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Deficient Transferrin for Detection of Alcohol Relapse After Orthotopic Liver Transplantation for Alcoholic Cirrhosis

Abstract: Early diagnosis and monitoring of an alcohol relapse in patients after orthotopic liver transplantation for alcoholic cirrhosis is of importance for the long-term outcome. A prospective study of 97 patients who underwent orthotopic liver transplant for alcoholic cirrhosis has been performed. All of the recipients considered for analysis survived for at least 3 months and were under the care of one specialist psychologist. Mean follow-up amounted to 48.5+/-1.4 months. The rates of alcohol relapse at 1 and 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Given that postal questionnaires are insensitive tools to detect very low levels of alcohol exposure, 6 it is possible that even this figure of a 50% relapse rate is an underestimate of the true frequency of alcohol relapse in these patients. Recent studies using objective markers of alcohol relapse, such as urinary alcohol levels, 28 serum carbohydrate-deficient transferrin concentrations, 29,30 or the degree of fat in liver biopsy specimens, 31 also suggest a considerable underreporting of alcohol use after liver transplantation for ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Given that postal questionnaires are insensitive tools to detect very low levels of alcohol exposure, 6 it is possible that even this figure of a 50% relapse rate is an underestimate of the true frequency of alcohol relapse in these patients. Recent studies using objective markers of alcohol relapse, such as urinary alcohol levels, 28 serum carbohydrate-deficient transferrin concentrations, 29,30 or the degree of fat in liver biopsy specimens, 31 also suggest a considerable underreporting of alcohol use after liver transplantation for ALD.…”
Section: Discussionmentioning
confidence: 99%
“…In the posttransplant follow-up, the examinations performed by the specialist psychologist were supported by prospective CDT monitoring. Excellent sensitivity and specificity could be demonstrated [5], indicating reliable rates for alcohol relapse. CDT was reassesed frequently enough for monitoring of drinking behavior, as it can safely be stated impossible for patients suffering from alcohol relapse not to drink alcohol for 17days (half-life of CDT) before a pending clinical visit.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, in patients with chronic liver disease CDT-TRI-SIALO (+) had a distinctly worse performance for the detection of recent alcohol consumption. Although some reports [24,25] found CDT-TRISIALO (+) useful even in patients with chronic liver disease, others [7,[26][27][28] showed a weak correlation of recent alcohol consumption with CDT levels only. Some authors reported a better positive predictive value for recent alcohol consumption with CDT-TRISIALO (+) than with γGT or MCV [7] whereas others found no advantage in using CDT-TRI-SIALO (+) than the latter markers of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%